Dietary rambutan peel powder as a rumen modifier in beef cattle - Ampapon, Thiwakorn (Asian-Australas J Anim Sci, 2020)
OBJECTIVE: The experiment was conducted to study the effect of rambutan (Nephelium lappaceum) fruit peel powder (RP) on feed consumption, digestibility of nutrients, ruminal fermentation dynamics and microbial population in Thai breed cattle. METHODS: Four, 2-year old (250±15 kg) beef bull crossbreds (75% Brahman×25% local breed) were allotted to experimental treatments using a 4×4 Latin square design. Four dietary supplementation treatments were imposed; non-supplementation (control, T1); supplementation of RP fed at 2% of dry matter intake (DMI) (low, T2); supplementation of RP fed at 4% of DMI (medium, T3) and supplementation of RP fed at 6% of DMI (high, T4). All cattle were given a concentrate supplement at 1% of body weight while Napier grass was provided as a free choice. RESULTS: The findings revealed that RP supplementation did not negatively affect (p>0.05) DMI of Napier grass, while RP intake and total DMI were the greatest in the RP supplementation at 4% and 6% DMI. Nevertheless, the nutrients (dry matter, organic matter, crude protein, neutral detergent fiber, and acid detergent fiber) digestibilities were not changed in the RP supplementation groups. Rumen fermentation parameters especially those of total volatile fatty acids, acetate and butyrate were not significantly changed. However, the propionate concentration was remarkably increased (p<0.05) in the RP supplementation. Notably, the ratio of acetate to propionate, the number of protozoa, as well as the methane estimation were significantly reduced in the RP supplemented groups (4% and 6% of DMI), while the counts of bacteria was not altered. CONCLUSION: Supplementation of RP (4% of DMI) improved rumen propionate production, reduced protozoal population and methane estimation (p<0.05) without a negative effect on feed consumption and nutrients total tract digestibilities in beef cattle. Using dietary rambutan fruit peel powder has potential promise as a rumen regulator.